Juridical Review of Notary Role in Fiduciary Insurance in PT. Andalan Finance Indonesia (Nasmoco Credit) Semarang - Nurcahyo Pratomo Widodo; Lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to analyze: 1) Implementation of the agreement with the Fiduciary PT. Andalan Finance Indonesia (Nasmoco Credit) Semarang. 2) The role of the Notary in the Deed of Fiduciary Manufacture PT. Andalan Finance Indonesia (Nasmoco Credit). 3) Obstacles and solutions in the manufacture of the Deed of Fiduciary PT. Andalan Finance Indonesia (Nasmoco Credit) Semarang.This research is research with empirical juridical approach. Specification of the research is descriptive. In this study, researchers obtained the primary data sources through interviews and field research object of research Nasmoco Credit and Notary in Semarang. The secondary data obtained through literature.The research results are: 1) Implementation of the agreement with the Fiduciary PT. Andalan Finance Indonesia (Nasmoco Credit) Semarang starting from the stage financing request of consumers, the application review consumer financing, the stages of recommendation, preparation of contract documents, disbursement of consumer financing, the stages of the agreement, the stages of the determination of insurance, the imposition of fiduciary, a deed to the notary and registration of fiduciary to fiduciary office. 2) The role of the Notary in the Deed of Fiduciary Manufacture PT. Andalan Finance Indonesia (Nasmoco Credit) Semarang is a Notary role in making authentic deed in the form of fiduciary deed in accordance with the provisions of the legislation as well as the notary office. 3) Barriers perceived by the notary that there are no obstacles for the data and procedures required by the notary had been prepared in full by both parties to undertake the financing agreement. This makes the notary does not have a bottleneck in the fiduciary deed. But for the problems in case of default Credit Nasmoco the path of deliberation, billing, administration subpoena or warning and the last way is a claim to court if there is no response from the Debtor.Keywords: Fiduciary; Agreements; Credit